Slaves of the Lord : the path of the Tamil saints - Dehejia, Vidya (New Delhi : Munshiram Manoharlal, 1988)
Lives and poetry of Tamil saints.
Includes index.
Bibliography: p. [197]-202.
Mode of access: Internet.
Keywords: Hinduism -- India -- Tamil Nadu; Alvars; Nayanars; Hindu saints, Tamil